Work Motivation Factors Affecting Gen Z Employees’ Job Satisfaction and Engagement in the E-commerce Industry in HO CHI MINH City - Nguyen, Dieu Hoa (2025)
This study explores the factors influencing job satisfaction and engagement among Vietnamese Generation Z employees working in the E-commerce industry in Ho Chi Minh City. As the E-commerce sector continues to develop rapidly in Vietnam, understanding factors that motivate and engage this generation is essential to improve performance and reduce employee turnover for organizations. The research focuses on six key factors, including compensation and salary, work-life balance, work environment, collaborative culture, leadership style, and career growth opportunities. Data was collected using a qualitative approach through twelve semi-structured interviews to gain deep insights into the experiences and expectations of Gen Z employees. The results show that this generation is influenced more by fairness, emotional support, transparent communication and meaningful career paths. Participants also highlight the value of supportive teamwork, approachable leadership, and opportunities to learn and grow within the organization. At the same time, issues such as heavy workloads, unclear expectations, and unstable internal processes were found to negatively affect satisfaction and long-term engagement. The study provides valuable understanding of how Gen Z employees experience work in the E-commerce sector and offers practical guidance for HR managers and leaders seeking to build more supportive and engaging workplaces.